Healthy soils, healthy plants, healthy humans: A holistic exploration of sustainable intensification effects on farming systems in Malawi - Mathews, M. (University of Amsterdam, 2021)
Smallholder farmers in Malawi are faced with resource and space constraints, low soil fertility, and vulnerability to climatic shocks. This has led to poor nutritional standing of farmers and their households, and very little ability to break through experienced feedback loops that keep them locked in a state of food and resource insecurity. The connection between soil-land and the human-health axis is only recently gaining momentum, however promising programs focused on sustainable intensification (SI) have begun to be implemented in sub-Saharan Africa to address root causes that lead to multi-dimensional poverty. Approaches such as SI, aim to provide farmers with low-cost accessible technologies that have the potential to optimize spatial resource allocation, increase production, and harness natural processes to mend degraded soils. As there are many SI technologies the scope of this research was to understand the holistic effect that incorporating biologically nitrogen fixing legumes within crop configurations can have on a farm system. Specifically by looking at the differences in space allocated to legume intercropping in the form of legume-legume, maize-legume, and doubled-up legume rotations (DLR). Due to the complex and dynamic nature of farming systems, one change in management may lead to spillover effects throughout the entire farming system. Therefore it was essential that a systems approach was used to analyze not just lower scale processes within the soil, but also higher-level analysis at the household and farm level. To do this, the application of an innovative bio-economic model, FarmDESIGN was employed, which allows for the integration of data at multiple levels. A case study approach was taken between two treatment groups (a mother and baby farm) in Central Malawi, with an additional exploration component carried out to understand potential opportunities, tradeoffs, and synergies that exploratory farm configurations could generate. In the case study analysis of the two treatments, a clear trade off was seen between farms that adopt more space for cash crops, and those that adopt more space for legume-intercropping. With a greater area dedicated to cash crops associated with increased financial standing, but less improvement in soil organic matter and dietary energy yield. While the farm with more space allocated to legume intercropping, was associated with increased levels of environmental and nutritional standing, evidenced by the indicators of increased soil organic matter, and increased dietary energy yield. In exploratory runs the results show when optimizing holistic objectives of nutrition, economic, environment, and social standing the model allocates increased space to legume intercropping configurations. For the mother farm this was seen in increased area to DLR and for the baby farm, legume-maize area. It can be concluded from this that a farms holistic standing increases the more area there is dedicated to legume intercrops.